Sustainable Marketing in the Sharing Economy: Strategies for Promoting Responsible Consumption - ZIOBROWSKA-SZTUCZKA, Justyna; LEWANDOWSKI, Maciej (Journal of Environmental Management and Tourism; Vol 16 No 3 (2025): JEMT, Volume XVI, Issue 3(79), Fall 2025, 2025)
The study aims to analyze the role of sustainable marketing in supporting the development of the sharing economy. In particular, it focuses on its role in shaping consumer behavior, promoting the idea of responsible consumption, and building trust in sharing platforms. The explanatory research design enabled the identification of sustainable marketing activities of the selected companies. The study used purposive sampling, selecting four sharing economy companies representing different segments related to urban mobility: Lime, BlaBlaCar, Traficar and Bolt. Data was obtained from the official websites of these entities. A qualitative methodological approach was used to comprehensively assess the communication strategies of the sharing platforms within a specifically defined framework. Our results indicate that sustainable marketing is key in promoting sharing platforms as tools to support the transition to a low-carbon economy and more responsible consumption patterns. The study also highlights challenges such as authenticity in communications and building long-term consumer trust. Purposive sampling limits the possibility of generalizing the results. Analysis is based solely on materials published by the companies themselves, which may lead to an incomplete picture of reality, as firms may selectively present information, highlighting positive aspects of their activities. Assessing the impact of communication strategies on consumer behavior poses a methodological challenge due to the lack of direct data from consumers. Findings and recommendations from the study can contribute to a better understanding of how to effectively use sustainable marketing to promote the sharing economy and achieve sustainable development goals.